The Aceh Separatism Conflict in Indonesia The Practice of Governance in Conflict - Susan, Novri (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book is the first to analyse the practice of governance to resolve conflict in the case of Aceh in Indonesia. Combining theoretical discourse on conflict, democracy, and governance, it draws from original field research on the separatist conflict, utilizing a social constructivist approach in collating observations and interviews with political elites from both the Government of Indonesia and the Aceh Independent Movement (GAM). The conflict was an intractable one in which thousand civilians were killed between 1976 and 2006. The author zooms into the 2003 and 2007 period, against the broader context of the political landscape of Indonesia under the Suharto regime. In doing so, the book tackles the challenges presented by intrastate conflicts relating to ethno-religiosity, land use, and separatism. It unpacks the Indonesian political system's shift from an authoritarian regime to a democratic one, and demarcates the prevalence of state violence in managing conflicts, as exemplified in the Aceh separatism conflict. Relevent to political scientists and scholars in peace, conflict and development studies, this co-published book presents novel sociological insights into Indonesia's historical, and contemporary, political landscape.
Chapter 1 The Polarization In Post-Conflict Society -- Chapter 2 Democratic Governance In Conflict -- Chapter 3 Road To Peace: From Coercive To Democratic Governance In Conflict -- Chapter 4 The Social Construction Of Reintegration Process In Aceh Post Conflict -- Chapter 5 The Contribution Of Democracy To Governance In Conflict.
Keywords: Peace; Political sociology; Economic development; Asia -- Politics and government; Asia -- History; Peace and Conflict Studies; Political Sociology; Development Studies; Asian Politics; Asian History